(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2019)
In this article author discusses the play/performance of Andrzej Sadowski Mayakovski reactivation. In the structure of the performance, he notices elements of the poet’s biography, elements taken from a computer game, elements referring to Majakowski’s texts (intertext). All this makes the performance become a kind of game with Majakowski’s texts and at the same time plays with contemporary conventions, expressed in the form of virtual reality. It also creates a reality referring to alternative history